Comparative study of tympanoplasty using endomeatal approach using tragal cartilage and perichondrium with postauricular approach using temporalis fascia graft - Yamuna, Katari; ., Teja; Lanke, Sowmya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic suppurative otitis media is a disease which is a major cause of morbidity in our country. A large proportion of patients have safe (mucosal) chronic suppurative otitis media which leads to ear discharge and deafness which hampers the productivity of many individuals. Otolaryngologists play an important role in its correction and amelioration by conservative or operative procedures. One such procedure is tympanoplasty. Methods: Patients of either sex having symptoms and signs suggestive of chronic suppurative otitis media and fulfilling the inclusion and exclusion criteria are taken for the study My sample size is 60 and these 60 patients were divided into 2 groups. A. tympanoplasty with temporalis fascia graft. B. tympanoplasty with cartilage island graft. 30 patients were included in each group. Results: In the cartilage island group, the graft uptake rate was 96.7% as compared to the temporalis fascia group in which the same was 90%. There is no significant difference in Air Bne gap between 2 groups. Conclusions: Cartilage Island graft is as good a graft material as temporalis fascia for tympanoplasty.